(untitled) (Journal of Forestry, 2025)
Forest fires are a significant environmental challenge, impacting ecosystems, biodiversity, and human communities. Over the past decade, research on forest fire mapping and management has surged, reflecting the urgent need for effective strategies to mitigate these risks. This review examines the relation between the mapping and management of forest fires from 2013 to 2023 using a bibliometric analysis based on the PRISMA framework. The Scopus database was selected for its extensive range of publications, ensuring comprehensive coverage of relevant research. An initial search identified 927 documents, which were refined to 240 publications through specific inclusion and exclusion criteria. The analysis reveals a notable increase in publications since 2019, highlighting the most productive journals, authors, institutions, and countries in this field. Key findings include the identification of leading research hubs and influential contributors, as well as emerging trends and prevalent keywords. The growing number of literature underscores the critical role of mapping and managing forest fires, particularly in the context of global climate change and its exacerbating effects on fire incidence and severity. This review provides valuable insights into the evolving landscape of forest fire research, emphasizing the importance of continued innovation and collaboration.